Heterodox analysis of financial crisis and reform : history, politics and economics - Leclaire, Joelle (Edward Elgar Publishing Ltd. CheltenhamGB, 2011)
Questions whether financial system regulations can be reformed. Deals with the history and underpinnings of financial crises. Gives insight into how financial crises are linked to the international system and to the welfare of developing nations. Provides macro, micro and international perspectives on the nature of these crises and their possible solutions.